Electronic Sterilization of Tableware Using Ultraviolet Light Radiation - Farros Zuhri Ramdhani; Didik Riyanto Riyanto; Desriyanti Desriyanti (Muhammadiyah University, Sidoarjo, 2020)
The hospital is one of the health service institutions that conducts complete individual health services that provide inpatient, outpatient and emergency services. Where in the hospital is also a gathering place for many people, namely the patient and also the patient's family. This is also a factor that bacteria and microorganisms can grow rapidly. As found on the patient's tableware. Because the tableware used continuously and alternately will make bacteria grow faster, especially if the process of washing the cutlery is less clean. From this problem emerged the idea to design a tool